Management of small testicular masses: outcomes from a single‐centre specialist multidisciplinary team. (21st September 2022) - Wardak, Shafi; Pang, Karl H.; Castiglione, Fabio; Lindsay, Jamie; Walkden, Miles; Ho, Dan Heffernan; Kirkham, Alex; Hadway, Paul; Nigam, Raj; Rees, Rowland; Alifrangis, Constantine; Alnajjar, Hussain M.; et al.
Abstract : Objectives: To report the management outcomes of men with ≤20‐mm small testicular masses (STMs) and to identify clinical and histopathological factors associated with malignancy. Patients and methods: A retrospective analysis of men managed at a single centre between January 2010 and December 2020 with a STM ≤20 mm in size was performed. Results: Overall, 307 men with a median (interquartile range [IQR]) age of 36 (30–44) years were included. Of these, 161 (52.4%), 82 (26.7%), 62 (20.2%) and 2 men (0.7%) underwent surveillance with interval ultrasonography (USS), primary excisional testicular biopsy (TBx) or primary radical orchidectomy (RO), or were discharged, respectively. The median (IQR) surveillance duration was 6 (3–18) months. The majority of men who underwent surveillance had lesions <5 mm (59.0%) and no lesion vascularity (67.1%) on USS. Thirty‐three (20.5%) men undergoing surveillance had a TBx based on changes on interval USS or patient choice; seven (21.2%) were found to be malignant. The overall rate of malignancy in the surveillance cohort was 4.3%. The majority of men who underwent primary RO had lesions ≥10 mm (85.5%) and the presence of vascularity (61.7%) on USS. Nineteen men (23.2%) who underwent primary TBx (median lesion size 6 mm) had a malignancy confirmed on biopsy and underwent RO. A total of 88 men (28.7%) underwent RO, and malignancy was confirmed in 73 (83.0%) of them. The overall malignancy rate in the whole STM cohort was 23.8%. Malignant RO specimens had significantly larger lesion sizes (median [IQR] 11 [8–15] mm, vs benign: median [IQR] 8 [5–10] mm; P = 0.04). Conclusions: Small testicular masses can be stratified and managed based on lesion size and USS features. The overall malignancy rate in men with an STM was 23.8% (4.3% in the surveillance group). Surveillance should be considered in lesions <10 mm in size, with a TBx or frozen‐section examination offered prior to RO in order to preserve testicular function.